ICT APPLICATIONS IN TOURISM AND HOSPITALITY INDUSTRY OF BANGLADESH: A RESEARCH REVIEW - Sardar, Sazu; Hossain, Dr. Md. Enayet; Kamruzzaman, Dr. Md.; Ray, Rudrendu (IJRDO - Journal of Business Management, 2021)
The ICT application in the tourism and Hospitality Industry (THI) is not a new phenomenon in advanced countries. Despite having the immense importance of ICT in the tourism and hospitality industry, many countries are yet to reasonable use especially in developing countries like Bangladesh. Thus, this study is highly emphasized in exploring the usage patterns of ICT in THI. An extensive literature review has been done and content analysis techniques have been applied in this study to attain the research objectives. The analysis reveals that the ICT plays an important role in the real life of the tourism and hospitality industry. It is found that ICT is used for e-marketing, e-strategic management, ensuring security and rendering tourism and hospitality services which are also applicable in Bangladesh. In fact, the application should recognize five factors- Organizational, Technical, Economic, Environmental and Personal. The contributors of the study are expecting that the outcome of the study will help to construct a framework that could be supportive to improve the present condition of ICT application and will also open a new horizon for destination operators and policymakers for formulating effective tourism and hospitality development policies and strategies in tourism and hospitality industry in Bangladesh.